2018
DOI: 10.1002/cbdv.201800282
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Toxicity of Asparagus Saponins in Distinct Multidrug‐Resistant Colon Cancer Cells

Abstract: Colorectal cancer is the third most common cancer in the world. Many efforts have focused on finding natural molecules with potential chemo-preventive activity due to their low toxicity compared to synthetic drugs. However, comprehensive information on the bioactive fractions and components is still missing. In this study, we developed a method for the quantitative separation and isolation of saponins from asparagus genotypes consisting of an adsorption chromatography and subsequent liquid chromatographic sepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…The results of previous studies confirmed that a saponin extract and methanol extract of asparagus have some toxic effects on CRC cells ( Bousserouel et al, 2013 ; Jaramillo-Carmona et al, 2018 ). Similarly, the results of the present study showed that an aqueous extract of asparagus significantly decreased the proliferation of HCT116 and LOVO human colorectal cancer cells.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The results of previous studies confirmed that a saponin extract and methanol extract of asparagus have some toxic effects on CRC cells ( Bousserouel et al, 2013 ; Jaramillo-Carmona et al, 2018 ). Similarly, the results of the present study showed that an aqueous extract of asparagus significantly decreased the proliferation of HCT116 and LOVO human colorectal cancer cells.…”
Section: Discussionsupporting
confidence: 56%
“…The anticancer activity of polysaccharide, saponin, and flavonoid extracts from ASP has been reported in various cancers, such as lung and bladder cancer ( Bilušić et al, 2019 ), liver cancer ( Cheng et al, 2021 ), and ovarian cancer ( Xu et al, 2021 ). Some studies have found that asparagus saponin extracts have significant cytotoxic effects on colorectal cancer cells ( Jaramillo-Carmona et al, 2018 ), and the results of Bousserouel ( Bousserouel et al, 2013 ) and others have shown in more detail that methanolic extracts of ASP can induce apoptosis by activating the TRAIL death receptor pathway in SW480 and SW620 human colon adenocarcinoma cells. However, the anticancer effects and mechanisms of ASP on colorectal cancer have not been determined systematically.…”
Section: Discussionmentioning
confidence: 99%
“…The health properties of asparagus include anti-microbial, antioxidant, and cytotoxic activities [152]. Asparagus extracts have illustrated a potent cytotoxic effect against colorectal cancer [153]. Treatment of Myeloid-derived suppressor cells (MDSCs) with asparagus polysaccharide have shown a significant increase in apoptosis through intrinsic pathways and a significant decrease in cellular proliferation [154].…”
Section: Asparagusic Acidmentioning
confidence: 99%
“…(Akubugwo et al, 2007;Venskutonis & Kraujalis, 2013) Several papers have been published showing the cytotoxic effect of lectins and extracts rich in lectins on normal and malignant cells (Reynoso-Camacho et al, 2003;Gonzalez de Mejia et al, 2005;. Likewise, trypsin inhibitors, tannins, and saponins, from different plant sources, have also been shown to have cytotoxic activity in several cell lines (Akhtar et al, 2017;Buyukleyla et al, 2012;Jaramillo-Carmona, Guillén-Bejarano et al, 2018;Jaramillo-García, Trindade et al, 2018;Mbaveng et al, 2018;Shamsi et al, 2017;Zhu et al, 2018). Saponins, trypsin inhibitors, and tannins from different sources have been reported as genotoxic, inducing the formation of micronuclei and chromosomal aberrations (Akhtar et al, 2017;Blaszkowska et al, 2009;Buyukleyla et al, 2012;Dauer et al, 2003;Demma et al, 2013).…”
Section: Hoursmentioning
confidence: 99%